A Novel, Intelligent, Pressure‐Sensing Colostomy Plug for Reducing Fecal Leakage. Issue 6 (16th January 2015) - Chen, Fei; Li, Zhi‐chao; Li, Qiang; Liang, Fei‐Xue; Guo, Xiong‐bo; Huang, Zong‐hai
Abstract This study aims to describe and report the effectiveness of a novel, pressure‐sensing colostomy plug for reducing fecal leakage. Nine miniature Tibetan pigs, aged 6–8 months, were given colostomies and divided into three groups (n = 3 each group). A novel pressure‐sensing colostomy plug was placed in each pig and set to indicate when intestinal pressures of either 5, 10, or 15 mm Hg, respectively, were reached. When the pressure thresholds were reached, the animals' bowels were examined for the presence of stool and/or stomal leakage, and the data were recorded at weeks 1, 4, and 8 after surgery. The colostomy plug calibrated to 15 mm Hg pressure demonstrated the greatest accuracy in predicting the presence of stool in the bowels of study animals, averaging >90% sensitivity. In general, the sensitivity for predicting the presence of stool did not vary significantly over time, though there was a slight increase in accuracy in the 5 mm Hg group at later time‐points. The sensitivity for predicting stool in the bowel did not change significantly over time in any of the three groups. Stomal leakage was found to be inversely proportional to the pressure‐sensor setting, in that the 15 mm Hg group exhibited the greatest amount of leakage. This difference, however, was found to be significant only at week 1 postsurgery. The intelligent, pressure‐sensing colostomy plug was able to accurately predict the presence of stool in the bowel and maintain continence, allowing negligible leakage.